Os colegas de classe na escola ubíqua: integração currículo, tecnologias digitais e mobilidade em contextos Brasil e Uruguai - Silva, Jayson Magno da (2017)
This PhD research, called The classmates at the ubiquitous school: curriculum integration, digital technologies and mobility in Brazilian and Uruguayan contexts, aims to establish relationships between the curriculum construction/reconstruction and development with the use of portable computers with connection opportunity and mobility potential in two different contexts of public schools, one in Brazil and another in Uruguay, in what concerns the pedagogical action. It starts with the question: Where is the curriculum? and is based on theoretical concepts from the perspective of integrating technologies into the curriculum and the emergence of the web curriculum. The research selected a public school where the program “Piraí Digital” (public policy of the Piraí city, in the state of Rio de Janeiro, Brazil, with Municipal Scope) is applied and another public school, located in the Eastern Republic of Uruguay, where the program “Plan Ceibal”, with national scope, is applied, as studies objects. Both public policies foresee the use of portable computers in the model 1-1 (one to one), with connection opportunity and mobility potential, in the context of education. In terms of methodology, this is a qualitative research with field research experiences and the use of the Grounded Theory as a methodological way to the data codification and analysis, supported by the software NVivo 11, used to organize the results. There are three groups of searched subjects- the officials: technicians of the central organs of both countries and the school principals and members of their team; the researchers: those who works in two universities of each nation and the main subjects: a primary school teacher from a public school in the capital, Montevideo, and her class of students, and an elementary school teacher (early years) from a public school in the municipality of Piraí and her class of students. The analysis of the results in each two different contexts area are shown in two articulated phases: the first one with substantive codification of the data, where it was found 22 different themes linked and flagged by indicators in each of the contexts and the second one, presenting the emergency of the theoretical basis of the grounded theory. The conclusion is that the use of portable computers in education, with opportunity of connection and mobility potential, allows the expression of the main subjects – teachers and students – to the (re)construction and development of the curriculum, going apart from the classroom and outweighing the barriers of their walls, putting the school in any place or time and giving it the context of the ubiquitous school, indicating the emergence of the web curriculum